Fibroma ameloblástico: relato de caso - Lauro Nunes da Rosa; Carlos A. Franco Neto; Heloisa Fontoura; Onofre Quadros (Revista da Faculdade de Odontologia de Porto Alegre)
A case of Ameloblastic Fibroma appearing in the posterior part of the mandible is presented. The histopathologic, roentgenologic and clinical aspects are discussed. The rapid growth and the size acqui red are emphasized. The treatment is conservative but the tumor needs close follow up for possible recurrence.